THE IMPACT OF DIGITALIZATION ON CARGO INSURANCE SERVICES IN UZBEKISTAN (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2024)
Digitalization is revolutionizing industries worldwide, including the insurance sector. In Uzbekistan, cargo insurance services are beginning to adopt digital tools, transforming how policies are issued, monitored, and claimed. This article explores the current state of digitalization in cargo insurance, its benefits for stakeholders, challenges to implementation, and prospects for future development in Uzbekistan